2013
DOI: 10.1371/journal.pone.0077525
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Antimicrobials in Pigs, Veal Calves, and Broilers in The Netherlands: Quantitative Results of Nationwide Collection of Data in 2011

Abstract: In 2011, Dutch animal production sectors started recording veterinary antimicrobial consumption. These data are used by the Netherlands Veterinary Medicines Authority to create transparency in and define benchmark indicators for veterinary consumption of antimicrobials. This paper presents the results of sector wide consumption of antimicrobials, in the form of prescriptions or deliveries, for all pig, veal calf, and broiler farms. Data were used to calculate animal defined daily dosages per year (ADDD/Y) per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(122 citation statements)
references
References 20 publications
7
114
0
1
Order By: Relevance
“…This is in agreement with findings reported in an earlier study performed in Switzerland [18]. The usage patterns reported in this study differ from those found in other countries, where tetracyclines are more commonly used than sulphonamides [13, 19, 20]. A possible explanation could be that Swiss pig farmers were discouraged from using certain antimicrobials, including tetracyclines, in the past and SGD members are still discouraged from using certain antimicrobials, including tetracyclines, without carrying out further diagnostics.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with findings reported in an earlier study performed in Switzerland [18]. The usage patterns reported in this study differ from those found in other countries, where tetracyclines are more commonly used than sulphonamides [13, 19, 20]. A possible explanation could be that Swiss pig farmers were discouraged from using certain antimicrobials, including tetracyclines, in the past and SGD members are still discouraged from using certain antimicrobials, including tetracyclines, without carrying out further diagnostics.…”
Section: Discussionsupporting
confidence: 92%
“…In the Netherlands an independent institution sets benchmarks for antimicrobial usage, which are re-evaluated on a yearly basis. Farms that exceed these benchmark levels are obliged to decrease their consumption by implementing measures [13]. Since the introduction of this program in 2012, antimicrobial consumption has been reduced by 56 % compared to consumption in 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Although we have to acknowledge that the confidence interval of this association was wide, its significance directly calls for the well-known causal evidence attributed to the use of these drugs for the emergence of ESBLs [2,18]. Most of the farms in this study did not use cephalosporins, which is comparable to the use in the Dutch pig farm population in the same period (2011–2013) [11,14]. We can conclude that for curbing ESBL numbers, reducing or restricting the use of cephalosporins was more decisive than an overall AMU reduction.…”
Section: Discussionmentioning
confidence: 65%
“…A more detailed description on the calculation of DDDA/Y is described in the Netherlands Veterinary Medicines Authority report and by Bos et al[11,14]. Data on AMU for the farms in this study have been described elsewhere [16].…”
Section: Methodsmentioning
confidence: 99%
“…In 2012 cattle followed. Usage on farms is expressed as animal daily dosages per year (add/y) (Bos et al 2013), which resembles the Danish system of reporting. 3 In this way farms and vets can be benchmarked and compared with each other and with independently defined targets (benchmarking).…”
Section: Reducing the Use Of Antimicrobials In Veterinary Practicementioning
confidence: 99%